2018
DOI: 10.1002/hep.30034
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic cancers are the leading cause of death in patients achieving hepatitis B virus control or hepatitis C virus eradication

Abstract: Compared to the general French population, HCV cirrhosis is associated with a higher risk of EHC and the first cause of death in patients with viral cirrhosis who achieve virological control/eradication. (Hepatology 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
(30 reference statements)
1
26
0
1
Order By: Relevance
“…79 Recently, an increased age-adjusted incidence of EHC was reported in French patients with HCV cirrhosis compared with that in the general population (standardised mortality ratio [SMR] 1.31; 95% CI 1.04-1.64). 80 This increase was even greater in those who had previously achieved SVR (SMR 1.57; 95% CI 1.08-2.22) (Fig. 2D).…”
Section: Extrahepatic Cancersmentioning
confidence: 85%
See 1 more Smart Citation
“…79 Recently, an increased age-adjusted incidence of EHC was reported in French patients with HCV cirrhosis compared with that in the general population (standardised mortality ratio [SMR] 1.31; 95% CI 1.04-1.64). 80 This increase was even greater in those who had previously achieved SVR (SMR 1.57; 95% CI 1.08-2.22) (Fig. 2D).…”
Section: Extrahepatic Cancersmentioning
confidence: 85%
“…EHC was the leading cause of death in the CirVir cohort in patients who achieved SVR. Reproduced from Nahon et al, 14,57 Allaire et al 80 and Cacoub et al 75 with permission. BI, bacterial infection; DAA, direct-acting antiviral; EHCs, extrahepatic cancers; SVR, sustained virological response.…”
Section: Identification Of Cirrhotic Patients With a Higher Residual mentioning
confidence: 99%
“…27 A recent study reported that patients with viral hepatitis have a 30% higher risk of extrahepatic cancer compared with the general population. 28 With the expected decline in liver-related complications during the era of antiviral agents, the improved longevity in individuals with viral hepatitis has been marred by rising mortality from extrahepatic complications, now representing the fourth most common cause of death in the overall cohort and the leading cause in patients with viral eradication (HCV infection) or adequate viral suppression (HBV infection). 28 Several studies have suggested that chronic HCV infection or chronic HBV infection increases the risk of hematologic malignancy, particularly non-Hodgkin lymphoma and myelodysplastic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] However, cirrhotic patients who achieve SVR remain at risk of developing hepatocellular carcinoma 27 and extrahepatic cancers. 28 Additionally, reversal of cirrhosis after SVR seems to be a slow process and the alterations of the immune system may persist after achieving SVR, particularly in cirrhotic patients. 20 Previous studies have described a significant decrease, after SVR with HCV therapy, in peripheral memory T-cells 29 and immune activation (CD4 + CD38 + and CD8 + CD38 + ), [29][30][31] and in plasma levels of biomarkers related to inflammation (interleukin (IL) −6, IFN-γ -inducible protein 10 (IP-10)), 32 bacterial translocation (lipopolysaccharide binding protein, soluble CD14 (sCD14) and fatty acid-binding protein 2 (FABP2)), 30 , 32 and endothelial dysfunction (soluble tumor necrosis factor receptor-1 (sTNF-R1), soluble intercellular adhesion molecule 1 (sICAM-1) and soluble vascular cell adhesion molecule 1 (sVCAM-1)).…”
Section: Introductionmentioning
confidence: 99%